The Existence of Basabali Wiki as A Multimodal Learning among Balinese Language Learners in Higher Education - Diari, Komang Puteri Yadnya (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
Advancements in digital technology have provided various opportunities for integrating innovative platforms like BASAbali Wiki into language learning, particularly in higher education.